2003
DOI: 10.1177/0954008303015004005
|View full text |Cite
|
Sign up to set email alerts
|

6F-Polyimides with Phenylethynyl Endcap for 315-370 °C Applications

Abstract: 6F-Polyimides with a phenylethynyl endcap (HFPE) were fabricated into carbon fiber composites using the standard polymerization of monomer reactant (PMR) approach via the ester/acid route. T650-35/HFPE carbon fiber composites were evaluated against the corresponding T650-35/PMR-II-50 composites with nadic endcap at 315ï370 C (600ï700 F) for their physical and mechanical properties as well as thermo-oxidative stability. In addition, concentrated HFPE monomer solutions were infused into stitched AS4 and T650-35 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 7 publications
1
37
0
Order By: Relevance
“…For example, fluorination of methylene carbon of MDA should thus prevent the oxidation of MDA, and similarly for the end‐caps. Fluorinated PMR variants are shown to have lower weight loss than the native polymers, in agreement with our conclusions.…”
Section: Resultsmentioning
confidence: 92%
“…For example, fluorination of methylene carbon of MDA should thus prevent the oxidation of MDA, and similarly for the end‐caps. Fluorinated PMR variants are shown to have lower weight loss than the native polymers, in agreement with our conclusions.…”
Section: Resultsmentioning
confidence: 92%
“…The amide acid oligomers were synthesized by the reaction of calculated stoichiometric ratios of anhydride (a‐BPDA), amino (2,5‐bis(4‐aminophenoxy)‐biphenyl), and macrocycle (2) in DMAc and subsequently cyclo dehydrated by chemical imidization to obtain macrocycle‐terminated oligomers. Many works showed that reducing average molecular weight by changing the stoichiometry and diamine composition of oligomers owned a profound effect on the processability of the uncured oligomers and T g value after cross‐linking . In this article, the monomers used for synthesizing the polyimide oligomers were varied to study the influences of molecular weight on the cross‐linking properties.…”
Section: Resultsmentioning
confidence: 99%
“…The carbon fiber tape was obtained from Cytec composites. HFPE-II-52 resin is a NASA-developed polyimide [12]. The samples were prepared by first making a prepreg sheet of carbon fibers and HFPE-II-52 resin.…”
Section: Laminate and Sample Fabricationmentioning
confidence: 99%
“…The intralaminar shear strength reflects the strength of the matrix and/or the shear strength of the fiber-matrix bond and can be affected by residual stresses [10] and moisture [11]. This study focuses on composites made from T650-35 graphite fibers with HFPE-II-52 matrix, a polyimide developed for use in composite materials [12]. The limited published data available on HFPE-II-52 and its composites include [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation